Effectiveness of Happiness-Based Psychotherapy on Life Quality and Self-Compassion in Patients with Multiple Sclerosis - Esmaeil-Beigi, Fatemeh; Hosseini , Saedeh Al-Sadat (Iranian Journal of Neurodevelopmental Disorders, 2024)
Objective: This study aimed to investigate the effectiveness of happiness-based psychotherapy (HBT) on the quality of life (QoL), self-compassion of individuals with Multiple Sclerosis (MS). Methods and Materials: In a quasi-experimental design, 50 MS patients were randomly assigned to either an experimental group (HBT intervention) or a control group. The intervention consisted of 12 weekly sessions focused on increasing self-compassion and happiness through therapeutic techniques. Data were collected at baseline (pre-intervention) and post-intervention using standardized self-report measures assessing QoL (MSQoL-54), self-compassion (Self-Compassion Scale), and happiness (Subjective Happiness Scale). ANCOVA was used to analyze the differences between the groups while controlling for baseline measures. Findings: The results indicated that the experimental group showed significant improvements in all dimensions of QoL (physical health, mental health, social relationships, and environmental health) as well as self-compassion, compared to the control group. The ANCOVA revealed that the experimental group’s improvements were statistically significant, with large effect sizes for all outcomes. These findings suggest that HBT can enhance both emotional and physical aspects of well-being in MS patients. Conclusion: Happiness-based psychotherapy appears to be an effective intervention for improving the emotional well-being and quality of life of individuals with MS. Enhancing self-compassion and happiness through this therapeutic approach may provide a valuable tool in managing the psychological burdens of chronic illness and improving overall well-being in MS patients.